Geochemistry of snow cover in taiga and alpine permafrost landscapes in Yakutia - V. N. Makarov (Лëд и снег, 2015)
The work is devoted to results of study the chemical composition of snow in mountain taiga and permafrost landscapes of Yakutia. We studied snow cover in different mountain-belt types of landscapes. The composition and calculated volumes of chemical elements and compounds are studied in snow. The chemical composition of snow in mountain taiga and permafrost landscape has remained relatively constant (hydrocarbonate chloride-bicarbonate or sodium-calcium, low sulfate content). The dominant influence on the chemical composition of snow at plains and mountain permafrost landscapes has a continental origin, mainly carbon compounds. In mountain desert, where there is predominantly regional transfer, along with the carbon significant role in atmospheric precipitation in cold season belongs to the nitrogen compounds, mainly ammonium. The total density of the entry of soluble and insoluble components in the form of snow decreases regularly with change of altitude. The distribution of trace elements in the snow cover is not a subject to altitudinal zonation. The maximum content of heavy metals (Mn, Cu, Pb, Cd), F, and Sr in the snow cover is observed in the landscapes of mountain woodlands and mountain tundra, where the route crossed research Sette-Daban metallogenic zone of stratiform Cu and Pb-Zn mineralization.